Difficulties of Q Fever Diagnostic Verification at Negative PCR Testing Results - Ya. D. Yankovskaya; T. A. Chekanova; M. V. Kutateladze; K. Petremgvdlishvili; T. Ya. Chernobrovkina (SINAPS LLC, 2023)
Aim of the work: to demonstrate the difficulty of verifying the diagnosis of Q fever with negative results of PCR (DNA of Coxiella burnetii) in the blood and to assess the occurrence of serological markers among patients selected for this study based on a combination of clinical and epidemiological data. Materials and methods: plasma/serum samples of 111 patients according to clinical and epidemiological data studied due ELISA and PCR for specific antibodies to Coxiella burnetii and DNA of pathogen. Additionally, in the presence IgG to C. burnetii phase II, IgG / IgA to phase I and the avidity of specific IgG were studied. Results: the specific antibodies to C. burnetii antigens at negative results of PCR detected in 10 cases. The article provides the description of three clinical cases for demonstration of difficulties of coxiellosis diagnosis with analysis of serological profiles, titers and avidity of antibodies. Conclusion: the results of the study indicate that negative results of PCR testing do not exclude C. burnetii infection. For patients who, according to clinical and epidemiological data, Q fever is not excluded, it is advisable to prescribe a complex of laboratory tests to verify the diagnosis, which includes not only studies of the pathogen's DNA, but also specific antibodies. To clarify the stage of the disease and reduce the risk of developing complications of coxiellosis, it is necessary to monitor the dynamics of antibody titers to C. burnetii in phase I and II phase states differentially.